Wall enhancement segmentation for intracranial aneurysm - Niemann Annika; Larsen Naomi; Preim Bernhard; Saalfeld Sylvia (Current Directions in Biomedical Engineering, 2020)
We present a tool for automatic segmentation of wall enhancement of intracranial aneurysms in black blood MRI. The results of the automatic segmentation with several configurations is compared to manual expert segmentations. While the manual segmentation includes some voxels of lower intensity not present in the automatic segmentation, overall the volume of the automatic segmentation is higher.